Mercury in the environment pattern and process - Bank, Michael S. (University of California Press, 2012)
"Mercury deposition and contamination is widespread and well documented, and it continues to be a public-health concern for certain sectors of the global human population in both developed and developing countries. This edited volume focuses on integrating the diverse sciences involved in the process of mercury cycling in the environment--from the atmosphere, through terrestrial and aquatic food webs, and human populations--to develop a comprehensive perspective on this important environmental pollutant. Using a systems-level approach, this book provides recommendations on mercury remediation, risk communication, education, and monitoring. In response to a growing need for understanding the cycling of this ubiquitous pollutant, the science of mercury has grown rapidly, expanding into several interdisciplinary fields and encompassing such disparate academic and scientific disciplines as biogeochemistry, economics, sociology, public health, decision sciences, physics, global change, and mathematics. Only recently have scientists really begun to establish more holistic approaches to studying mercury pollution, giving rise to investigations that have furthered the integration of a multi-tiered approach, especially by using chemistry, biology, and human health sciences collectively. The study of mercury pollution has produced a variety of contributions to domestic and international policies related to the management of mercury in the environment"--